The modeling Effect of Emotional Competence in Cyberbullying Profiles - Guerra Bustamante, Joan; Yuste Tosina, Rocio; Lopez Ramos, Victor; Mendo Lázaro, Santiago (Anales de Psicología / Annals of Psychology, 2021)
Emotional competencies are fundamental in preventing involvement in cyberbullying situations. The main goal of this research is to study the involvement profile in cyberbullying situations, according to the mediating effect of variables such as perceived emotional intelligence, gender and age in the adult population. To this end, measures are taken through self-reports exploring the profiles of cyberbullying and the dimensions of Perceived Emotional Intelligence (PEI), among a sample of 848 subjects enrolled in Massive Open Online Courses (MOOCs). Multivariate and binomial regression analyses are carried out, showing that the majority of participants who have difficulties in understanding and regulating their emotional states are involved in situations of cyberbullying, and pointing to emotional intelligence skills as a clear protective factor against cyberbullying. These results show the need to pay greater attention to the phenomenon of cyberbullying in the adult population, as well as the relevance of emotional intelligence skills in the prevention of cyberbullying.